SMART CAR - Tariq Salameh; Mohamed Qamhieh (My University, 2011)
SMART CAR Project : a car that uses artificial intelligence algorithms to think about solutions to get out of certain situations.SMART CAR Project : an artificial intelligence project depends on algorithms developed to make this car get out of any maze and then save the exit path so that it could choose the optimal path to the exit next time it faces the same maze.Why SMART CAR ?The main idea is to use artificial intelligence.Same Algorithms can be used to control much more complicated robots.Using of new technology based on a new microcontroller.

SMART CAR Project : a car that uses artificial intelligence algorithms to think about solutions to get out of certain situations. SMART CAR Project : an artificial intelligence project depends on algorithms developed to make this car get out of any maze and then save the exit path so that it could choose the optimal path to the exit next time it faces the same maze. Why SMART CAR ? The main idea is to use artificial intelligence. Same Algorithms can be used to control much more complicated robots. Using of new technology based on a new microcontroller.
SMART CAR